Douglas Henderson: from hard spheres to biological channels - Eisenberg, B.; Busath, D.; Trokhymchuk, A. (Condensed Matter Physics, 2005)
On August 7, 2004, the Henderson Symposium on Basic and Applied Statistical Mechanics of Condensed Matter was held at Brigham Young University in Provo, Utah. This Festschrift grew out of that occasion and includes some of the articles presented on that occasion, at which we also celebrated his 70th birthday.